Anatomical Study of Male Reproductive Organs of the Indonesian Short-Nosed Fruit Bat (Cynopterus titthaecheilus Temminck, 1825) - Anisatuzzahro Anisatuzzahro; Muhammad Jafar Luthfi (Biology, Medicine, & Natural Product Chemistry, 2017)
Bats are one of the mammals of Chiroptera order. Chiroptera Order has two sub-orders, Megachiroptera and Microchiroptera. One of the species of Megachiroptera is Cynopterus titthaecheilus (C. titthaecheilus). Local name for C. titthaecheilus is the Indonesian short-nosed fruit bat. Characteristics of C. titthaecheilus are dark brown body hair and no tragus in the ear. Population of C. titthaecheilus in Indonesia are relatively abundant,  but research about anatomy of male reproduction organs of this species is still rare. The purpose of this study was to determine the anatomical features of male C. tittahecheilus reproductive organs. Observations of macroscopic anatomy include observation of morphology, size, weight and volume of penis, testiscle, epididymis, vas defferens, prostate and seminal vesicles. Observation on microscopical anatomy of male reproduction organ is using histological slide preparations stained by Hematoxylin-Eosin.